Thinking with/in surfing: Podcasting as public pedagogy and scholarship in/for the global South - Thompson, Glen; Graaff, Karen (Critical Studies in Teaching and Learning, 2023)
This article introduces The Deep Duck Dive —a podcast engaging with the oceanic turn in the global South by focusing on issues that matter within surfing as a lifestyle sport. As co-hosts of the podcast, we have approached podcasting as forms of public pedagogy and public scholarship. Our aim is to increase the accessibility of scholarship and research by creating an alternative space for conversations with those outside of the academy. The article charts how we conceptualised and realised this podcast project as thinking with/in surfing. Within this epistemological approach, we seek to contribute to the intellectual currents of hydrocolonialism, hydrofeminism and critical surf studies, and to open our soundwork as an alternative pedagogical practice within justice-to-come public scholarship. To illustrate our podcasting style, reflexive of our positionalities as scholars and surfers, we have provided the transcript of our pilot episode.